Transcranial Direct Current Stimulation in Sport: Neurodoping or Performance Support? Systematic Review - Kałuża, Kinga; Pater, Michał; Kałwa, Natalia; Smerdzyński, Mateusz; Chmurska, Agnieszka; Majchrzyk, Aleksandra; Strzępek, Aleksandra; Łyżwa, Julia; Frączek, Karolina; Janaszek, Agnieszka (Quality in Sport, 2026)
Background. Professional athletes increasingly rely on neurophysiology to enhance athletic potential. Transcranial Direct Current Stimulation (tDCS) has become one of techniques to modulate cortical excitability. It can act as ergogenic aid by modifying motor control and fatigue perception. Aim.This systematic review analyzes the impact of tDCS on motor skills, physical endurance, and cognitive performance. It also addresses the ethical debate surrounding “neurodoping”. Materials and Methods. This systematic review was conducted following PRISMA guidelines. The search was conducted in PubMed and Web of Science, and Scopus. 62 publications were analyzed, published up to January of 2026. The review focused on anodal stimulation of M1 and DLPFC regions. Results. Findings indicate small to moderate effects on performance. The most consistent results involve reduced perceived exertion and improved Time-to-Exhaustion (TTE), especially in M1 stimulation. DLPFC stimulation showed benefits in cognitive tasks, decision-making, and emotional regulation. However, significant heterogeneity existed due to variations in study methodology. Conclusions. tDCS can enhance performance by modulating the perception of effort rather than increasing physical capacity. While not currently prohibited by WADA, the high variability in results shows need for standardized protocols and further research into longterm effects and ethical regulations.